Deteksi Keberadaan Penyebab Penyakit Citrus Vein Phloem Degeneration (CVPD) secara Molekuler pada Tanaman Jeruk Siam (Citrus nobilis Lour var. microcarpa Hassk) berdasarkan Variasi Gejala Klorosis - NURHAYATI, IKA; ADIARTAYASA, WAYAN; BAGUS, I GUSTI NGURAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Detection of the Presence of Citrus Vein Phloem Degeneration (CVPD) Disease Causing in Molecular on Citrus ( Citrus nobilis Lour var. microcarpa Hassk)which Based on Variation of Chlorosis Symptoms This research was aimed to identify the presence of Liberobacter asiaticum which caused of Citrus Vein Phloem Degeneration disease on citrus leave with different chlorosis symptoms. This research was conducted at Laboratory of Genetics Resources and Biology Molecular, Udayana University. The leaves sample were measured the chlorophyll content using a chlorophyll meter and then were identified in molecular using Polymerase Chain Reaction (PCR) technique, using primer O11 and O12 which will amplified the specific fragmen of 16S rDNA. The result for chlorophyll content indicated that the leaf samples were containing 26.80, 36.52, 36.62, 40.74, 44.56, 47,06, 58.44 and 65.16 SPAD.DNA amplification showed that the leaves which contained chlorophyll at 58.44 and 65.16 SPAD didn’t show DNA bands with size 1160 bp, and leaves which contained chlorophyll at26.80, 36.52, 36.62, 40.74, 44.56 and 47.06 SPAD showed DNA bands 1160 bp. Therefor the DNA bands 1160 bp is expression by L. asiaticum , then the citrus leaf samples were detected positive for the L. asiaticum and the samples were positive infected by CVPD disease, so that the chlorophyll content of citrus leaves at ?47.04 SPAD can be used as basis to diagnosis CVPD disease on citrus plants.
Keywords: CVPD; Liberobacter asiaticum; Chlorosis; PCR